Endoscopic and Histologic Features of Immune Checkpoint Inhibitor-Related Colitis. Issue 8 (27th April 2018) - Wang, Yinghong; Abu-Sbeih, Hamzah; Mao, Emily; Ali, Noman; Qiao, Wei; Trinh, Van Anh; Zobniw, Chrystia; Johnson, Daniel Hartman; Samdani, Rashmi; Lum, Phillip; Shuttlesworth, Gladis; Blechacz, Boris; et al.
Abstract: Background: Diarrhea and colitis are the second most common immune checkpoint inhibitor (ICPI)-induced adverse events. However, a comprehensive characterization of the endoscopic and histologic features of ICPI-induced diarrhea and colitis is lacking. Therefore, we aimed to describe endoscopic and histologic features of ICPI-induced gastrointestinal toxicities and to assess their association with patients' clinical characteristics and outcomes. Methods: We retrospectively reviewed records of 53 patients with ICPI-related diarrhea/colitis between 2011 and 2017. We collected data on demographics, diarrhea/colitis grade, treatment, and endoscopic and histologic findings. Long-term follow-up included repeat endoscopy findings, diarrhea recurrence, and overall survival. We compared groups by treatment, endoscopic and histologic findings, and constructed Kaplan-Meier survival curves. Results: Most patients had grade 2 or higher diarrhea (87%) and colitis (60%). Thirty-one patients were successfully treated with corticosteroids, and 22 additionally required infliximab. On endoscopy, 21 (40%) patients had ulcerations and 22 (42%) had nonulcerative inflammation. Patients with ulcerations had more steroid-refractory disease ( P = 0.044) and high-grade diarrhea ( P = 0.033). Histology showed mostly acute (23%) or chronic (60%) inflammation. During mean follow-up duration of 18.9 months, 19 (36%) developed recurrent diarrhea. Most patients had persistent endoscopic (8/13, 62%) and histologic (9/11, 82%) inflammation. Patients with higher-grade adverse events had improved survival. Higher-grade colitis was associated with endoscopic inflammation ( P = 0.039), but grade of diarrhea was not associated with endoscopic inflammation or grade of colitis. Conclusion: